Diversity oriented biosynthesis via accelerated evolution of modular gene clusters. Issue 1 (December 2017) - Wlodek, Aleksandra; Kendrew, Steve; Coates, Nigel; Hold, Adam; Pogwizd, Joanna; Rudder, Steven; Sheehan, Lesley; Higginbotham, Sarah; Stanley-Smith, Anna; Warneck, Tony; Nur-E-Alam, Mohammad; Radzom, Markus; et al.
Abstract Erythromycin, avermectin and rapamycin are clinically useful polyketide natural products produced on modular polyketide synthase multienzymes by an assembly-line process in which each module of enzymes in turn specifies attachment of a particular chemical unit. Although polyketide synthase encoding genes have been successfully engineered to produce novel analogues, the process can be relatively slow, inefficient, and frequently low-yielding. We now describe a method for rapidly recombining polyketide synthase gene clusters to replace, add or remove modules that, with high frequency, generates diverse and highly productive assembly lines. The method is exemplified in the rapamycin biosynthetic gene cluster where, in a single experiment, multiple strains were isolated producing new members of a rapamycin-related family of polyketides. The process mimics, but significantly accelerates, a plausible mechanism of natural evolution for modular polyketide synthases. Detailed sequence analysis of the recombinant genes provides unique insight into the design principles for constructing useful synthetic assembly-line multienzymes. Reengineering polyketide synthase encoding genes to produce analogues of natural products can be slow and low-yielding. Here the authors use accelerated evolution to recombine the gene cluster for rapid production of rapamycin-related products.